Unregulated saphenous vein graft distension decreases tissue viscoelasticity. (September 2017) - Wise, Eric S.; Hocking, Kyle M.; Evans, Brian C.; Duvall, Craig L.; Cheung-Flynn, Joyce; Brophy, Colleen M.
Objectives: Unregulated intraoperative distension of human saphenous vein (SV) graft leads to supraphysiologic luminal pressures and causes acute physiologic and cellular injury to the conduit. The effect of distension on tissue viscoelasticity, a biophysical property critical to a successful graft, is not well described. In this investigation, we quantify the loss of viscoelasticity in SV deformed by distension and compare the results to tissue distended in a pressure-controlled fashion. Materials and Methods: Unmanipulated porcine SV was used as a control or distended without regulation and distended with an in-line pressure release valve (PRV). Rings were cut from these tissues and suspended on a muscle bath. Force versus time tracings of tissue constricted with KCl (110 mM) and relaxed with sodium nitroprusside (SNP) were fit to the Hill model of viscoelasticity, using mean absolute error (MAE) and r 2 -goodness of fit as measures of conformity. Results: One-way ANOVA analysis demonstrated that, in tissue distended manually, the MAE was significantly greater and the r 2 -goodness of fit was significantly lower than both undistended tissues and tissues distended with a PRV (p<0.05) in KCl-induced vasoconstriction and SNP-induced vasodilation. Conclusions: Unregulated manual distension of SV graft causes loss of viscoelasticity and such loss may be mitigated with the use of an in-line PRV.